The Strategy of Maintaining Performance Image: Leverage, Firm Size, and Income Smoothing Practices - Putri Saphira; Atri Nodi Maiza Putra (Journal of Sharia Economics, Banking and Accounting, 2026)
This research investigates the influence of leverage and firm size on income smoothing practices among Logistics and Deliveries companies listed on the Indonesia Stock Exchange from 2022 to 2024. A quantitative method with a causal approach was applied in this study. The sample consisted of 10 companies selected through purposive sampling, generating 120 quarterly observations. Income smoothing was identified using the Eckel Index, while leverage was represented by the Debt-to-Equity Ratio (DER) and firm size was measured through the natural logarithm of total assets. The hypotheses were tested using binary logistic regression analysis. The findings reveal that leverage does not significantly influence income smoothing behavior. In contrast, firm size is negatively associated with income smoothing practices. These results imply that larger firms are generally subject to greater transparency requirements and stricter oversight, which may limit managerial incentives to smooth reported earnings.